ADMINISTRATIVE DECISIONS: CORRECTION THROUGH LEGISLATIVE POWER - Ahmad Aldaferi (Journal of Legal Studies & Research, 2022)
This article aims to find out whether Saudi legislator adopted method to post correct administrative decisions through legislation. The study used a critical comparative approach to clarify Saudi’s position concerning this issue. The study conducted that although the matter is common in some Arabic legal system such as Egyptian and Jordanian legislations. The current practices of Saudi legislation affirmed that legislator applied this exception approach in certain cases. The study concluded that post correction whether through legislative power or executive power should not be exercised broadly as it constitutes a breach of separation of power principle.